A review on stress inducement stimuli for assessing human stress using physiological signals - P., Karthikeyan; Murugappan, M., Dr.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org